Flexible protein nanofibrils fabricated in aqueous ethanol: Physical characteristics and properties of forming emulsions of conjugated linolenic acid. (May 2021) - Liu, Gang; Li, Wanrong; Qin, Xinguang; Zhong, Qixin
Abstract: Protein nanofibrils have recently shown unique properties preparing emulsions, with the stability improved after fibrillation of glycated proteins. The objective of the present study was to study physical and chemical properties of emulsions prepared with nanofibrils of different flexibility. Increasing ethanol level during heating aqueous whey protein isolate (WPI) solutions at pH 2.0 and 85 °C increased the amount of semiflexible and highly flexible worm-like nanofibrils, which was further increased for WPI glycated with lactose (gWPI). The increased abundance of worm-like nanofibrils and the increased hydrophobicity facilitated the adsorption and packing of the gWPI nanofibrils on oil droplets, which, together with the improved nanofibril thermal stability, improved thermal stability of conjugated linolenic acid (CLA) emulsions than the corresponding WPI nanofibril emulsions. The worm-like nanofibrils also improved the oxidative stability of CLA in emulsions. The present findings suggest protein nanofibrils with tunable material properties may be significant for functional foods applications. Graphical abstract: Image 1 Highlights: Highly flexible worm-like protein nanofibrils can be fabricated in aqueous ethanol at pH 2.0 and 85 °C. The worm-like nanofibrils facilitated the adsorption and packing on oil droplets. The nanofibrils on interfacial layer resulted in thermal stability improvement of CLA emulsions. The worm-like nanofibrils also improved the oxidative stability of CLA in emulsions.